Synthesis of heteroglycoclusters by using orthogonal chemoselective ligations - Thomas, Baptiste; Fiore, Michele; Bossu, Isabelle; Dumy, Pascal; Renaudet, Olivier (Beilstein Journal of Organic Chemistry, 2012)
Synthetic heteroglycoclusters are being subjected to increasing interest due to their potential to serve as selective ligands for carbohydrate-binding proteins. In this paper, we describe an expedient strategy to prepare cyclopeptides displaying well-defined distributions and combinations of carbohydrates. By using both oxime ligation and copper(I)-catalyzed alkyne–azide cycloaddition, two series of compounds bearing binary combinations of αMan, αFuc or βLac in an overall tetravalent presentation, and either 2:2 or 3:1 relative proportions, have been prepared.
Keywords: chemoselective ligation; click chemistry; cyclopeptide; heteroglycocluster; oxime